Interaction of Follicle-Stimulating Hormone and Stem Cell Factor to Promote Primordial Follicle Assembly in the Chicken - Guo, Changquan; Liu, Guang; Zhao, Dan; Mi, Yuling; Zhang, Caiqiao; Li, Jian (Frontiers in Endocrinology, 2019)
Follicle-stimulating hormone (FSH) and KIT signaling are required for ovarian development. In this study the interactive effect of FSH and stem cell factor (SCF) on folliculogenesis was investigated in the chicken. Correlated changes between the FSH receptor and the expression of KIT signaling genes were seen to be involved in the formation of the chicken primordial follicles. FSH and SCF displayed a reciprocal stimulating effect in the promotion of folliculogenesis involving elevated expressions of mitogen-activated protein kinases 1/3 (MAPK1/3) and protein kinase B (AKT) mRNAs. Knockdown of c-KIT or SCF reduced the stimulatory effect of FSH on KIT signaling as well as upon MAPK1 and AKT mRNA expression. Treatment of FSH and SCF in combination enhanced ovarian cell proliferation and N-cadherin expression, but inhibited cell apoptosis and E-cadherin expression. Overall, the reciprocal stimulating effect of FSH and SCF in promoting chicken follicle assembly involving accelerated ovarian cell proliferation, N-cadherin expression, inhibited cell apoptosis and E-cadherin expression is demonstrated.